MetALD: Genetic Factors and Clinical Outcomes - Israelsen, Mads; Trépo, Eric; Krag, Aleksander; Stender, Stefan (Seminars in Liver Disease, 2025)
Metabolic and alcohol-related liver disease (MetALD) is a subcategory of steatotic liver disease (SLD) characterized by the coexistence of cardiometabolic risk factors and elevated alcohol intake. The global prevalence of MetALD is estimated to be 2 to 5%, but this is likely underestimated due to self-reporting biases. In real-world settings, fluctuations in alcohol intake mean that many patients with SLD may be classified as having MetALD at some point during their disease. Although MetALD is relatively common, only a minority of patients with the disorder progress to advanced chronic liver disease. Genetic factors modulate disease initiation and progression, with risk variants in PNPLA3, HSD17B13, and TM6SF2 being particularly relevant. Polygenic risk scores incorporating these and other variants have demonstrated a potential for identifying at-risk individuals. This review comprehensively examines MetALD, covering its natural history, genetic underpinnings, clinical outcomes, the predictive potential of genetic risk scores, and future therapeutic avenues involving gene silencing.
Keywords: cirrhosis; polygenic risk score; hepatocellular carcinoma; fatty liver; nonalcoholic steatohepatitis